MODERATING EFFECT OF INTROVERSION AND EXTROVERSION ON THE RELATIONSHIP BETWEEN PARENTING STYLES AND EGO STRENGTH: Life Sciences-Psychology - REIHANEH FAYYAZ; ZAHRA SARMAST; FARIDEH AMERI; MOHAMMAD ALI BESHARAT (International Journal of Life Science and Pharma Research, 2022)
Ego strength plays a determinant role in individual’s psychological health. The aim of this study was to examine the potential effects of extroversion-introversion on the relationship between parenting styles and Ego strength. Therefore, 190 girls in third grade of high school completed Ego Strength Scale (ESS) and Eysenck Personality Questionnaire-revised (EPQ-RS). Also, one of the students parent were asked to complete the Baumrind Parenting Styles Questionnaire. Results revealed a significant positive correlation between authoritative parenting and Ego strength (R=0.29, p<0.01). Extroversion demonstrated a significant positive association with ego strength (p<0.01 ،R=0.21). As substantial through data analyses, the relationship between authoritative parenting and Ego strength was moderated by extroversion. It can be concluded that the relationship between authoritative parenting and Ego strength is not simply linear and potentially influenced by extroversion.